2017
DOI: 10.1088/1361-6668/aa6fbf
|View full text |Cite
|
Sign up to set email alerts
|

Strong anisotropy effect in an iron-based superconductor CaFe0.882Co0.118AsF

Abstract: The anisotropy of the Fe-based superconductors is much smaller than that of the cuprates and the theoretical calculations. A credible understanding for this experimental fact is still lacking up to now. Here we experimentally study the magnetic-field-angle dependence of electronic resistivity in the superconducting phase of iron-based superconductor CaFe0.882Co0.118AsF, and find the strongest anisotropy effect of the upper critical field among the iron-based superconductors based on the framework of Ginzburg-L… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…The large errors can be ascribed to errors in the sample dimensions, irregular sample shapes and inhomogeneous current distribution. The large anisotropy ρ c /ρ ab of the order of 10 2 is broadly consistent with the large upper-critical-field anisotropy of 9 observed for CaFe 0.882 Co 0.118 AsF [25] as the two anisotropies are approximated by m * c /m * ab and m * c /m * ab , respectively.…”
Section: Temperature Dependence Of Resistivitysupporting
confidence: 80%
“…The large errors can be ascribed to errors in the sample dimensions, irregular sample shapes and inhomogeneous current distribution. The large anisotropy ρ c /ρ ab of the order of 10 2 is broadly consistent with the large upper-critical-field anisotropy of 9 observed for CaFe 0.882 Co 0.118 AsF [25] as the two anisotropies are approximated by m * c /m * ab and m * c /m * ab , respectively.…”
Section: Temperature Dependence Of Resistivitysupporting
confidence: 80%
“…Here λ ab is the penetration depth within the ab plane. Moreover, the Fermi surfaces in the present system are nearly ideal cylinders 27,32 and the in-plane Fermi velocity is rather isotropic within the k x − k y plane. In this case, ρ ab s of the ith Fermi surface can be given by 36…”
Section: Resultsmentioning
confidence: 77%
“…Especially, it was found that the smaller FS around the Γ point (see the α FS in Fig. 4) is much smaller than other FSs around M point and consequently shows a worse nesting condition 27,32 , as compared with the other larger FSs, which should benefit the identification of the abovementioned itinerant and local mechanisms.…”
Section: Introductionmentioning
confidence: 98%
“…The resultant values for the three characteristic fields B ab c2 (in-plane B c2 ), B c c2 (out-of-plane B c2 ) and B P are denoted by arrows in Figure 1c and summarized in Table 1, from which the anisotropy of upper critical field Γ = B ab c2 /B c c2 = 11 is obtained. This value is larger than most of the iron-based superconductors and the copper-based superconductor YBCO 16,19 . Moreover, a clear relative relation B c c2 < B P < B ab c2 can be deduced.…”
Section: Introductionmentioning
confidence: 74%